Homoeopathic Management of Sub-acute Appendicitis—A Case Report - Nath, Arunava; Palit, Deb Kumar; Kundu, Nivedita; Lakshmi, S. Seetha (Homœopathic Links, 2022)
Sub-acute appendicitis is a condition where some episodes of acute appendicitis apparently subside spontaneously before they reach the acute stage. A 29-year-old man presented with pain in the right iliac fossa for the last 1 week with periumbilical radiation of pain associated with continual nausea, occasional bouts of vomiting, chill and rigours. Computed tomography scan report suggested a case of sub-acute appendicitis. On the basis of presenting features, the patient was treated with Belladonna and Calcarea carbonica in 30c and 200c (centesimal) potencies, respectively, with repetitions. The patient was under treatment for nearly 6 months with favourable improvement of the generalities along with the underlying pathology. The case was indicative of further studies with adequate sample size in such pathological condition to come to any decisive conclusion.
Keywords: sub-acute appendicitis; International Classification of Diseases—Clinical Modification; computed tomography; individualised homoeopathy